ANALISIS MODEL MANAJEMEN PERMINTAAN SCM NETWORK DAN PERAMALAN PERMINTAAN PADA PENJUALAN BUSANA MUSLIM MENGGUNAKAN METODE LINEAR REGRESSION - Vela Maghfiroh; Yusuf Amrozi; Qushoyyi Bondan Prakoso; Mochamad Adam Aliansyah (Universitas Methodist Indonesia, 2021)
Supply chain management is very important for a company because it will affect supply performance in the company. Doing business in this era has many challenges that must be faced, especially in the Muslim clothing business. The way to stabilize the demand diagram of the Muslim clothing business, retailers are required to manage the supply chain so that they can meet the total demand. The object of this research is Rabbani Cirebon which was obtained from a literature study published in a journal entitled